Review/PerspectiveTranslational Medicine: What is it and what could it be? - Wehling, Martin (Arzneimittelforschung, 2009)
Translational medicine is not a traditional and established discipline in the biosciences, certainly not in medicine. It has become a very popular phrase which is being more and more widely used in variable contexts both by the pharmaceutical industry, funding agencies and academia.The idea of translational medicine is as obvious as persuasive if introduced into grant applications or industry tools of operation. It is driven by the general observation that there is a deep and rapidly widening trench between medical in vitro and animal research on one hand and clinical innovation on the other. Whereas the knowledge in medicine in general terms is exploding, this does certainly not translate into an explosion of novelties in patient treatments, exceptions granted. In particular, the lamento is coming increasingly from the pharmaceutical industry which complains about surging R&D costs at yet steadily decreasing marketing approval rates of new medicines. Academia and its sponsors join into this choir not understanding why all the knowledge obtained in the test tubes and experimental animals (e. g. knock-out mice) does help so little in changing realities of daily medical practice. Thus, translation has become a widespread phrase to indicate that research and development aims at bedside innovation or facilitates the transition from ‘bench to bedside’. For this, it utilizes biomarkers which should be predictive at an early stage of development (e. g. animal experiments) for later stages, especially at the human level. Human exploratory (non-regulatory) trials are important tools for early proof of principle. In general, however, a clear set of methods and technology is still lacking, and no solid science supports the wish to translate. If biomedical research should survive increasing competition for resources by other areas of research demands from e. g. environmental or energy concerns, it has to get the act of translation right in that a solid armamentarium of paradigms, tools, methods needs to be created. This includes translation planning, translatability assessment, and, thus, portfolio considerations to balance translational risks in both public and private funding situations.
Keywords: Biomarkers; Paradigms; Translational assessment; Translational medicine